Computers, ethics, and society - Ermann, M. David (Oxford University Press, 2003)
In today's world, computers can have complex and contradictory effects on human life. They can enhance our quality of life by creating access to previously unimagined worlds. On the other hand, as computers become increasingly important in our everyday lives, their potential to strip away our privacy and autonomy increases exponentially. Computers, Ethics, and Society, now in its third edition, offers a comprehensive, interdisciplinary set of readings on the ethical and social implications of computer technology. Taking into account technological, social, and philosophical issues, the contributors consider topics such as the work-related ramifications of automation, the ethical obligations of computer specialists, and the threats to privacy that come with increased computerization